The Impact of Pulsed Electric Field Treatment of Beetroots on the Physicochemical Properties of Juice, Dried Juice, and Dried Pomace - Aleksandra Jedlińska; Alicja Barańska-Dołomisiewicz; Katarzyna Samborska; Katarzyna Rybak; Artur Wiktor; Dorota Witrowa-Rajchert; Małgorzata Nowacka (Applied Sciences)
The aim of this work was to determine the impact of pulsed electric field treatment of beetroots on select physicochemical properties of the obtained juice, spray-dried juice, and freeze-dried pomace. Pulsed electric field pretreatment of beetroots was conducted with a different number of pulses (3 or 44 pulses) at a constant electric field strength of E = 1.07 kV/cm, which resulted in the total energy levels of 0.5 and 4 kJ/kg. The juice was dehumidified and air spray-dried with NUTRIOSE® as a drying carrier at 90/60 °C, while pomace was freeze-dried at 0.63 Pa and a shelf temperature of 20 °C. Pulsed electric field (PEF) treatment caused an increase in pigment content in beetroots and the juice. In the case of powders, the following effects were noted: a decrease in drying efficiency, changed powder color, decreased powder particle diameter. Dried juice and pomace treated with a higher pulsed electric field (PEF) treatment were characterized by the highest hygroscopicity.